Ritual Clowns and Laughter in the Religions of the Nepalese Himalayas: The Symbolic Language of Transgressive Sacrality - Toffin, Gérard (Anthropologica, 2019)
This research explores the comical performances that are staged in the Nepal Himalayas on certain dates of the year fixed by the religious calendar. On these occasions jesters and tricksters turn the ritual performance into a joyful and laughable event and become the very heart of the rituals. The study focuses on the two most closely associated central figures of Indo-Nepalese Hindu culture: Brahmans (and world-renouncing ascetics) and kings. These key characters, who stand at the top of the caste hierarchy, are duly mocked and lampooned for their supposed faults: they are false, greedy, liars, gluttons. Their pranks include disguising as transvestites, illicit behaviour, and scatological gestures. I argue that these farcical events and rituals of inversion display the dark side of religion and express in a theatrical way enduring conflicts between the positive and the negative forces of the universe or between the material plane and transcendental entities that are believed to rule the world. The upside-down elements (mundus inversus) are clearly expressed in these sketches. However, the disorder and confusion exhibited during them remain within the boundaries of social norms.